CRLMDA: CRL minimisation and distribution algorithm in cluster-based VANETs. (7th February 2023) - Singh, Dinesh; Maurya, Ashish Kumar; ,; Yadav, Rama Shankar
The certificates of vehicles identified as malicious must be revoked and placed in the certificate revocation list (CRL). The large size of CRL is an overburden on revocation process of malicious vehicles. This paper proposes an algorithm called CRL minimisation and distribution algorithm (CRLMDA) to minimise CRL in cluster-based VANETs. The algorithm monitors the use of certificates during communication. To avoid lazy processing, a cluster head (CH) vehicle informs the certificate authority about the certificate. The CH vehicle that identifies a vehicle as malicious immediately initiates a local and global revocation process to avoid mishappening in network function. Our algorithm compresses the CRL using Bloom filter and distributes it to the other vehicles via roadside units and the CH vehicles. The reported results show that the CRLMDA algorithm performs better in revocation overhead and CRL distribution delay than HHL and SCRLE algorithm.